Technomobility in China : Young Migrant Women and Mobile Phones - Wallis, Cara (Book collections on Project MUSE., 2013)
As unprecedented waves of young, rural women journey to cities in China, not only to work, but also to "see the world"and gain some autonomy, they regularly face significant institutional obstacles as well as deep-seated anti-rural prejudices. Based on immersive fieldwork, this book provides an intimate portrait of the social, cultural, and economic implications of mobile communication for a group of young women engaged in unskilled service work in Beijing, where they live and work for indefinite periods of time. While simultaneously situating this work within the fields of feminist studies, technology studies, and communication theory, the author explores the way in which the cell phone has been integrated into the transforming social structures and practices of contemporary China, and the ways in which mobile technology enables rural young women - a population that has been traditionally marginalized and deemed as "backward" and "other" - to participate in and create culture, allowing them to perform a modern, rural-urban identity. In this theoretically rich and empirically grounded analysis, the author provides original insight into the co-construction of technology and subjectivity as well as the multiple forces that shape twenty-first century China.--description adapted from publisher's website.